Bonding Effectiveness of Two Adhesive Luting Cements to Glass Fiber Posts: Pull-Out Evaluation of Three Different Post Surface Conditioning Methods - Lorenzo Graiff; Laura Rasera; Marco Calabrese; Paolo Vigolo (International Journal of Dentistry)
The purpose of this study was to evaluate the bond strength at the post/resin-cement interface with 3 different surface treatments of glass fiber posts and with 2 different luting resin cements. Sixty glass fiber posts (RelyX Fiber Post) were randomly divided into 3 groups (n=20) and were luted with a dual-polymerizing self-adhesive universal resin cement (RelyX Unicem) and with a dual-polymerizing resin cement (RelyX ARC). This was carried out in association with a dual-polymerizing adhesive (Scotchbond Multi-Purpose Plus) in simulated plexiglass root canals after receiving three different pretreatment procedures. A pull-out test was performed on each sample to measure bond strengths. Data were analyzed with two-way ANOVA. Two samples from each group were processed for SEM observations in order to investigate the morphologic aspect of the post/cement interface. Both resin cements demonstrated significant different bond strength values (P<0.0001). The surface treatment result was also statistically significant (P=0.0465). SEM examination showed a modification of the post surface after pretreatment with methyl methacrylate. The dual-polymerizing self-adhesive universal resin cement achieved higher MPa bond strength values. The use of methyl methacrylate as a surface treatment of glass fiber posts provided a significant increase in bond strengths between the posts and both luting materials.